Bee diversity and pollination services improve with revegetation effort - Kireta, D.; Lowe, A. J.; Guerin, G. R.; Leijs, R.; Hogendoorn, K. (Austral ecology, 2024)
Habitat loss is causing declines in native bees and reducing pollination services. Revegetation can be used to reverse these declines, and this restoration technique attracts growing efforts and resources. However, how the quality of revegetation affects native bee abundance, diversity and their pollination services is not well understood, and this limits opportunities to improve revegetation outcomes. To assess this gap, we surveyed floral and bee diversity in revegetated landscapes ranging in habitat quality, and compared these among each other and to remnant habitat and cleared areas. We also measured pollination services using two native phytometer species, which can be pollinated by native bees only, or by both native and introduced honey bees (Apis mellifera). We found that bee diversity and richness were higher within treatments that were higher in floral diversity. In addition, while pollination services provided by honey bees were uniform across treatments, remnant vegetation supported greater pollination services to the plant species pollinated by native bees only. These results indicate that higher quality revegetation characterized by the establishment of a more diverse set of plant species, has the potential to restore native bee diversity and associated pollination services. However, for the plant species investigated, restoration of pollination services had not occurred and might require more time. These results suggest preserving remnant vegetation should be the highest priority conservation action, and that restoration practitioners and landowners wishing to support landscape‐level bee diversity and pollination services, should aim for revegetation using high flowering plant diversity.